Diagnostic and therapeutic approaches to multiple myeloma patients: ‘Real-world’ data from representative multicentre treatment surveys in Germany between 2008 and 2011 - Möhler, Thomas; Merz, Maximilian; Goldschmidt, Hartmut (Oncology letters, 2016)
A survey was conducted to investigate the standard of care for multiple myeloma in Germany, in order to clarify the status of implementation of international and national treatment guidelines. In addition, the changes in disease management over time were investigated by comparison with surveys conducted in 2008 and 2009. The survey captured a representative sample of 478 myeloma patients with a mean age of 67.9 years across various stages of the disease. Diagnostic approaches, prognostic aspects and treatment decisions were evaluated based on a survey conducted in 2011 in 58 representative centres in Germany, including university and non-university hospitals and office-based haematologists. Data were collected from chart reviews and were analysed retrospectively. Over time, an increasing number of patients were investigated for cytogenetic abnormalities (53%). Age <69 years and lack of comorbid conditions were major determinants for cytogenetic testing. Bortezomib/chemotherapy-based regimens have become the preferred first-line treatments independent of planning autologous blood stem cell transplantation (ASCT) in first-line therapy. Thalidomide- and lenalidomide-based combination therapies are typically used as second-line treatments in 31% of patients. Compared with previous reviews, the frequency of ASCT was stable, at ~30% of patients. Younger age and indicators of more severe disease, such as the presence of CRAB criteria, influenced the decision in favour of performing ASCT. Compared to previous surveys, the requirement for erythropoietin and granulocyte colony-stimulating factor, as well as transfusions of red blood cells and platelets, respectively, have decreased considerably. In summary, novel agents have led to a substantial change in the first-line and relapsed treatment approaches. Age and comorbidities remain major factors influencing treatment decisions, but cytogenetic testing to investigate myeloma-related risk profiles is increasingly integrated. The use of novel agents has affected supportive care, with reduced necessity for substitute blood products and reduced administration of bone marrow-stimulating factors.